Performance of Self-Compacting Concrete Slab with Grinded Local Rocks (Journal of Engineering, 2018)
The effect of using grinded rocks of (quartzite and porcelanite) as powder of (10 and 20) % replacement by weight of cement for self-compacting concrete slabs was investigated in this study. Five slabs with 15 concrete cubes were tested experimentally at 28 days to study the compressive strength, ultimate load, ultimate deflection, ductility, crack load and steel strain. The test results show that, the compressive strength improvement when replacement of local rock powder reached to (7.3, 4.22) % for (10 and 20) % quartzite powder and (11.3, 16.1) % for (10 and 20) % porcelanite powder, respectively compared to the reference specimen. The ultimate load percentage increase for slabs with (10 and 20) % replacement of quartzite powder was 41.17% and 23.53%, while the slabs with (10 and 20) % replacement of porcelanite powder were 23.53% and 35.3% compared to the reference slab, respectively. The ultimate deflection, ductility, spread cracks and ultimate steel strain for slabs with replacement materials (quartzite and porcelanite) increased significantly compared to the reference slab.